Amino acid effects on heterocyclic amine formation in the Maillard reaction model systems and pan-fried beef patties - Linghu, Ziyi (Kansas State University, 2019)
Heterocyclic amines (HCAs) are a group of highly mutagenic and potentially carcinogenic compounds that typically form on cooked meat through the Maillard reaction. While many physical factors, such as heating temperatures/times and cooking methods, and using food additives with antioxidant properties can affect HCA formed in the Maillard reaction, modifying HCA precursor profiles, such as types and concentrations of amino acids before heating, is a relatively new discovery and could effectively minimize dietary HCA formation in cooked meat. Simple liquid Maillard model systems were first conducted to evaluate the effect of eight essential and two non-essential amino acids (AAs) on 2-amino-1-methyl-6-phenylimidazo [4,5-b]pyridine (PhIP) formation. Each AA was individually added into model systems (glucose: creatinine: phenylalanine) and mixtures were heated at 180 °C for 1 h. Tryptophan, lysine, leucine, and proline exhibited the most pronounced inhibitory effects (> 87% reduction) on PhIP formation, followed by methionine, valine, isoleucine, threonine, and phenylalanine at the highest molar ratio; while aspartic acid increased PhIP formation. The inhibition mechanism for this reaction was investigated in phenylacetaldehyde-AA model systems (180 °C /1 h), which showed that formation of phenylacetaldehyde-AA adducts may be responsible for the reduction in PhIP formed during Maillard reaction. A simple, fast, and efficient method based on Enhanced Matrix Removal of Lipids (EMR-Lipid) was then developed for identifying trace-level HCAs in cooked meats that ranged from high-protein (beef and chicken) to high-fat (pork bacon) matrices. Liquid chromatography-tandem mass spectrometry (LC-MS/MS) with selective reaction monitoring mode was used for qualitative and quantitative analysis. Good linearity of standard curves was obtained in both pure solvents and post-spiked meat extracts between 0.5 and 50.0 ng/mL. Satisfactory recoveries of four HCAs were achieved in a range of 65 to 111% in beef, 71 to 106% in bacon, and 42 to 77% in chicken. For the first time, this work demonstrates that EMR-Lipid coupled with LC-MS/MS may be a promising option for polar HCA extraction and detection in fatty meat products. To further study the inhibitory effect of selected amino acids on HCA formation in cooked meat, tryptophan, lysine, leucine, and proline at 0.05%, 0.20%, and 0.50% (w/w) were investigated in pan-fried beef patties (230 °C/15 min). Tryptophan at 0.50% showed the most reduction on total HCAs (93% inhibition), followed by 0.50% lysine (84% inhibition), while leucine and proline at 0.50% were less effective. Several key flavor compounds of fried beef, such as aldehydes and various pyrazines, were affected by added AAs at 0.50%. Surface application of most AAs had no significant effect on cooking loss, pH, or color change in fried beef patties; however, adding lysine increased pH and surface redness. Overall, the results of this study suggest that adding amino acids to ground beef patties could effectively mitigate mutagenic HCA formation during cooking.
Keywords: Heterocyclic amine; Amino acid; Pan-fried beef patties; Maillard reaction